The Logic of Conspiracy Theories in the Internet Day - Ольга Васюта; Сергій Васюта (Історико-політичні проблеми сучасного світу)
The paper reviews the logic of conspiracy theories in the age of internet, emphasizing that the spread of internet usage increased the amount and variety of political information, which has created unprecedented opportunities to communicate with supporters about current events. The wide availability of content provided by users on online social media makes it easier to connect people around common interests, beliefs and narratives. However, the internet also allows you to quickly spread anecdotal rumors and conspiracy theories, which often cause fast, large, but often naive social responses. It is the internet that allows conspiracy theories to travel farther and faster than before. Belief in conspiracy theories reduces trust in traditional media and government institutions, even if they are not associated with conspiracy theories.